Low temperature spin-glass magnetic behavior of Ce₃Pd₂₀Ge₆ - Gaidukov, Yu.P.; Nikiforov, V.N.; Koksharov, Yu.A.; Szymczak, R.; Szymczak, H.; Gribanov, A.V. (Физика низких температур, 1998)
A polycrystalline sample of Ce₃Pd₂₀Ge₆ is investigated using a dc SQUID magnetometer. A noticeable difference between ZFC and FC magnetic susceptibility is found below ≈60 K. The temperature dependence of the magnetic susceptibility demonstrates an anomaly near approximately 2.8K below which a remanent magnetic moment exists. Two characteristic temperatures detected support the assumption that there are different cerium magnetic subsystems in Ce₃Pd₂₀X₆ (X= Ge,Si) compounds. Unusual magnetic behavior observed in Ce₃Pd₂₀Ge₆ is discussed within the framework of the "molecular magnetism" model which predicts a frustration of exchange interactions.